2015
DOI: 10.1111/head.12562
|View full text |Cite
|
Sign up to set email alerts
|

Headache, Cerebral Aneurysms, and the Use of Triptans and Ergot Derivatives

Abstract: Associations between some headaches and aneurysms may exist. Some chronic headaches may respond to surgical aneurysm repair while others may worsen. These associations are undefined by current literature because of variable results, study methods, and limited data. Prospective studies are needed which incorporate pre- and post-procedure headache character and diagnosis, aneurysm characteristics, type of aneurysm repair, associated risk factors for worsening post-procedure headache, and ultimately combining all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 117 publications
0
16
0
Order By: Relevance
“…Several studies have reported headache improvement after such procedures, but many studies have reported incidences of worsening or new-onset headaches ranging between 10% and 55%. [3][4][5][6][7][8] In ICHD-3 beta, Chapter 6.7.1, headache attributed to an intracranial endovascular procedure appears to be based primarily on small-sample studies, most of which were conducted more than 20 years ago [9][10][11][12] (Table 1). Moreover, these studies were based on local anesthesia that was generally used in carotid or vertebral embolizations or angioplasties.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported headache improvement after such procedures, but many studies have reported incidences of worsening or new-onset headaches ranging between 10% and 55%. [3][4][5][6][7][8] In ICHD-3 beta, Chapter 6.7.1, headache attributed to an intracranial endovascular procedure appears to be based primarily on small-sample studies, most of which were conducted more than 20 years ago [9][10][11][12] (Table 1). Moreover, these studies were based on local anesthesia that was generally used in carotid or vertebral embolizations or angioplasties.…”
Section: Introductionmentioning
confidence: 99%
“…63 Case reports involving triptan-related cerebrovascular complications in this patient group do exist but provide no definite support for causality. 63 Case reports involving triptan-related cerebrovascular complications in this patient group do exist but provide no definite support for causality.…”
Section: Expert Commentarymentioning
confidence: 88%
“…63 Case reports involving triptan-related cerebrovascular complications in this patient group do exist but provide no definite support for causality. 63 A study of 12,339 migraineurs using injectable sumatriptan reported no intracranial hemorrhages over a 1-year period,as about 5% of the general population has an asymptomatic aneurysm, this can be interpreted as at least somewhat reassuring, 65,66 In regard to AVMs, evidence is scarce. 64 In a retrospective series of 10 patients with untreated and 10 with coiled aneurysms who were using triptans, no complications occurred.…”
Section: Expert Commentarymentioning
confidence: 88%
See 2 more Smart Citations